IMPROVE THE SENSORY AND MOTOR ABILITIS OF CHILDREN USING EDUCATIONAL GAMES AGE 5-7 YEARS IN PRIMARY SCHOOL 24 RAMBUTAN - Agustian, Berry; Mawardah, Mutia (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
This service was carried out at the State Elementary School 24 Rambutan, Durian Gadis Village, Banyuasin district. Data collection techniques using observation, documentation, action, and reflection are used to collect data. The child's learning results and the analysis of the sensory and motor skills of the child in learning with the learning of numbers and letters through the combination of educational learning models and play models are carried out to know the speed of development by observing the child after being given home tasks in accordance with the rules that have been determined. The results showed an improvement in fine motor, auditory, visual, and gross motor skills in which the child’s activity meets the criteria of being highly active and the development of the sensory motor aspects of the child reaches the expected indicators of success. The results of this dedication show that the child's development in the State Elementary School 24 Village Durian Gadis Prefecture district of Banyuasin has been optimal.